ANALISIS HASIL BELAJAR KIMIA SISWA YANG DIBELAJARKAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING BERMEDIA POWERPOINT MELALUI PENDEKATAN SAINTIFIK PADA POKOK BAHASAN REDOKS - SILABAN, RAMLAN; TARIGAN, ELYSARANI BR; ALEXANDER, IRVING JOSAFAT (Jurnal Ilmu Pendidikan Indonesia, 2018)
This study aims to find out the chemistry learning outcomes of students with the completeness of the value of Minimum Completion Criteria (KKM), knowing the students 'social attitudes in the learning process, knowing the differences in learning outcomes, the correlation between students' social attitudes toward learning outcomes, and which models are most effectively used in learning models in giving a high contribution to student learning outcomes and students' social attitudes. The study was conducted on class X students of SMA 1 Tigapanah Karo Regency. The results showed that the percentage of students' completeness scores from experiment 1 was 75%, experiment 2 and experiment 3 were 45.83%. The percentage value of experimental 1 social attitudes which belong to the high category is 54.2% and which is categorized as quite 45.8%. The value of students' social attitudes from experiment 2 which belong to the high category is 58.8% and those that are classified as sufficient categories are 41.2%. The value of the students' social attitudes from experiment 3 which belong to the high category is 66.7%, which is categorized as quite by 29.2%, and which is classified as a category of less than 4.1%. The difference in posttest values that experimental learning results 1 (73.13)> experimental class 2 (67.29)> experimental class 3 (66.88) and social attitudes of students in each class can be seen from the average score of students' social attitudes, namely (70.44)> experiment 2 (69.12)> experiment 3 (69.79). There is a correlation between social attitudes and learning outcomes in each class. Teaching with the Problem Based Learning model with powerpoint media through the most effective Scientific Approach is used in teaching to students as evidenced by the highest average learning outcomes of 73.13 and the average value of student learning outcomes is 70.44. Keywords: Problem Based Learning, Powerpoint, Scientific Approach, Redox